Exome sequencing reveals FAM20c mutations associated with fibroblast growth factor 23–related hypophosphatemia, dental anomalies, and ectopic calcification - Rafaelsen, Silje Hjorth; Ræder, Helge; Fagerheim, Anne Kristine; Knappskog, Per; Carpenter, Thomas O; Johansson, Stefan; Bjerknes, Robert (Journal of bone and mineral research, 2013)
ABSTRACT Fibroblast growth factor 23 (FGF23) plays a crucial role in renal phosphate regulation, exemplified by the causal role of PHEX and DMP1 mutations in X‐linked hypophosphatemic rickets and autosomal recessive rickets type 1, respectively. Using whole exome sequencing we identified compound heterozygous mutations in family with sequence similarity 20, member C (FAM20C) in two siblings referred for hypophosphatemia and severe dental demineralization disease. FAM20C mutations were not found in other undiagnosed probands of a national Norwegian population of familial hypophosphatemia. Our results demonstrate that mutations in FAM20C provide a putative new mechanism in human subjects leading to dysregulated FGF23 levels, hypophosphatemia, hyperphosphaturia, dental anomalies, intracerebral calcifications and osteosclerosis of the long bones in the absence of rickets.